2007
DOI: 10.1016/j.ejcts.2007.09.017
|View full text |Cite
|
Sign up to set email alerts
|

Staging and resection of lung cancer with minimal invasion of the adjacent lobe☆

Abstract: The prognosis of NSCLC with limited invasion of an adjacent lobe was found to be similar with that of T3 tumors. A resection type lesser than a pneumonectomy may be considered in these tumors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
43
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(48 citation statements)
references
References 4 publications
4
43
1
Order By: Relevance
“…Normally, VPI indicates biological tumor invasiveness and is associated with a poor outcome. 3,4,7,9 Although we evidenced a pN0 rate of 58%, other authors reported that pN0 is generally inferior to 50% of cases, whereas nodal involvement is present in more than twothird of patients as a result of drainage of invading tumor into the adjacent lobe lymphatic system. By penetrating two different layers of the visceral pleura, tumors invading the fissure have a high probability to invade small lymphatic ducts and blood vessels.…”
Section: Discussioncontrasting
confidence: 52%
See 1 more Smart Citation
“…Normally, VPI indicates biological tumor invasiveness and is associated with a poor outcome. 3,4,7,9 Although we evidenced a pN0 rate of 58%, other authors reported that pN0 is generally inferior to 50% of cases, whereas nodal involvement is present in more than twothird of patients as a result of drainage of invading tumor into the adjacent lobe lymphatic system. By penetrating two different layers of the visceral pleura, tumors invading the fissure have a high probability to invade small lymphatic ducts and blood vessels.…”
Section: Discussioncontrasting
confidence: 52%
“…On the contrary, Okada et al 4 and Demir et al 7 suggested that NCSLC with FI had similar survival to that of T3 tumors. On the contrary, a lower survival was advocated by Okada et al, 4 Demir et al, 7 and Riquet et al 11 which showed a similar 5-year OS (respectively 37%, 36%, and 38.9%). As well, previous data on survival rates are discordant.…”
Section: Discussionmentioning
confidence: 96%
“…Demir et al 7 reported the survival of patients with this type of disease who underwent pneumonectomy was worse than in those who did not receive pneumonectomy. However, Yang et al 4 found a better survival rate in patients who underwent pneumonectomy, as compared to those receiving lesser resections.…”
Section: Discussionmentioning
confidence: 99%
“…According to the seventh edition of TNM classification and the TNM supplement of the Union for International Cancer Control (UICC), tumors invading the fissure to the adjacent lobe with diameter of less than 7 cm were classified as T2 2,3 . However, survival dispute arises in the T category of NSCLC invading the fissure to the adjacent lobe–ambiguity exists when classifying NSCLC with such a fissure invasion as T2 or T3 47 .…”
Section: Introductionmentioning
confidence: 99%
“…Bilobectomy itself may be associated with increased morbidity and mortality because of the increased complexity associated with resection of an additional lobe rather than Fig. 4 Disease-free survival of patients with complete resection (no residual tumor) by lobectomy, bilobectomy, or pneumonectomy after CCRT resection of a nonanantomic portion of an adjacent lobe [19,20]. We conclude that, compared to a lobectomy, a bilobectomy is associated with high operative mortality and poor long-term survival after neoadjuvant concurrent chemoradiotherapy for N2-stage IIIA NSCLC.…”
Section: Discussionmentioning
confidence: 99%